A petrographic study of carbonate phases in the Ulten Zone ultramafic rocks: insights into carbonation in the mantle wedge and exhumation-related decarbonation - Förster, Bibiana; Braga, Roberto; Aulbach, Sonja; Lo Pò, Deborah; Giuseppe Maria Bargossi, Giuseppe Maria; Mair, Volkmar (Ofioliti, 2017)
We present a comprehensive petrographic study on carbonates in orogenic mantle wedge-derived peridotites from the Ulten Zone (UZ) in the Eastern Italian Alps representing a fragment of the Variscan belt. These peridotites are found in ultramafic bodies incorporated in high-grade crustal rocks from a former continental slab and are characterized by highly variable mineral assemblages and microstructures, which reflect their evolution from spinel peridotite in a hot mantle wedge, to garnet peridotite after incorporation into the subducting slab and finally exhumation accompanied by retrogression. Carbonate phases in UZ peridotites are observed in diverse textural sites and can be related to particular petrographic peridotite types. Inclusions of dolomite and dolomite-breakdown products in primary spinel from coarse-grained protogranular peridotites indicate that carbon-bearing liquids were introduced into the mantle wedge at a time before achieving garnet stability. Discrete dolomite grains occur in fine-grained deformed garnet-bearing peridotite and are suggested to have formed simultaneously with hydrous phases (amphibole, apatite) from a carbon-bearing aqueous crustal slab-derived fluid during garnet stability. Intergrowths of calcite and brucite occur mainly in serpentinized fine-grained garnet-amphibole peridotites and are interpreted to be products of dedolomitization (CaMg(CO3)2 + H2O → CaCO3 + Mg(OH)2 + CO2), thus decarbonation, during exhumation. Veins of dolomite and calcite-brucite indicate secondary dolomite formation from carbon-bearing fluids due to interaction with slab-derived crustal fluids during retrogression on the exhumation path of the UZ peridotite. Magnesite veins and calcite veins that are texturally linked to alteration features are probably of low-temperature origin. In summary, this petrographic study reveals multi-stage carbonation of the UZ peridotites during residence in the mantle wedge and decarbonation with the release of a carbon species during low-temperature peridotite reaction with aqueous fluids leading to serpentinization accompanied by dolomite breakdown, thus providing important constraints on the carbon budget and carbon cycling in collisional settings. Overall, the ubiquity of carbonates in a variety of textural settings in the UZ peridotites suggests that the supra-subduction zone mantle in continental settings represents an efficient carbon trap.